The Influence of Determining Factors on Islamic Stock Index in Indonesia - Azhar Alam; Galuh Thifal Anggraeni; Muhammad Anas (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2020)
This paper investigated some determining factors that influence Indonesia Sharia Stock Index (ISSI). Some macroeconomic variables are used as an independent variable such as central bank interest rates, inflation, currency exchange rate, and return rates of Bank Indonesia Sharia Certificates (SBIS). This study conducted the Error Correction Model (ECM)  to analyze times series data during October 2013 and September 2017. The findings showed that Indonesia Sharia Stock Index (ISSI) is influenced significantly and negatively by central bank interest rates in long term analysis. Similarly, in short term analysis, the central bank interest rates affect significantly and negatively on ISSI as well as the currency exchange rates. On the other hand, SBIS return rates and inflation are indicated to have a non-significant negative effect on ISSI. This study suggested that investors of ISSI consider Central Bank interest rates, inflation, rupiah exchange rates, and SBIS rates of return to predict the stock price so investors can make the right decisions in their investment policies. This paper also recommended the Indonesian Central Bank to effectively manage their monetary policy and promote ISSI as an alternative investment which is resistant by the negative effect of inflation in short term analysis.